A bivalent recombinant vaccine targeting the S1 protein induces neutralizing antibodies against both SARS‐CoV‐2 variants and wild‐type of the virus. Issue 3 (17th May 2021) - He, Cai; Yang, Jingyun; He, Xuemei; Hong, Weiqi; Lei, Hong; Chen, Zimin; Shen, Guobo; Yang, Li; Li, Jiong; Wang, Zhenling; Song, Xiangrong; Wang, Wei; et al.
Abstract: The emerging variants of severe acute respiratory syndrome coronavirus‐2 (SARS‐CoV‐2) in pandemic call for the urgent development of universal corona virus disease 2019 (COVID‐19) vaccines which could be effective for both wild‐type SARS‐CoV‐2 and mutant strains. In the current study, we formulated protein subunit vaccines with AS03 adjuvant and recombinant proteins of S1 subunit of SARS‐CoV‐2 (S1‐WT) and S1 variant (K417N, E484K, N501Y, and D614G) subunit (S1‐Mut), and immunized transgenic mice that express human angiotensin‐converting enzyme 2 (hACE2). The S1 protein‐specific antibody production and the neutralization capability for SARS‐CoV‐2 and B.1.351 variant were measured after immunization in mice. The results revealed that the S1‐Mut antigens were more effective in inhibiting the receptor‐binding domain and ACE2 binding in B.1.351 variant than in wild‐type SARS‐CoV‐2. Furthermore, the development of a bivalent vaccine exhibited the ideal neutralization properties against wild‐type and B.1.351 variant, as well as other variants. Our findings may provide a rationale for the development of a bivalent recombinant vaccine targeting the S1 protein that can induce the neutralizing antibodies against both SARS‐CoV‐2 variants and wild‐type of the virus and may be of importance to explore the potential clinical use of bivalent recombinant vaccine in the future. Abstract : The bivalent recombinant vaccine composed of S1 subunit of SARS‐CoV‐2 and S1 variant (K417N, E484K, N501Y, and D614G) subunit could induce the neutralizing antibodies against both SARS‐CoV‐2 variants and wild‐type of the virus.